PENGARUH KEPEMIMPINAN DAN PEMBERDAYAAN PEGAWAI TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA PADA KINERJA PEGAWAI PDAM TIRTANADI PROVINSI SUMATERA UTARA - T. FAKHRI NOOR ANSHARI JOHAN (JURNAL ILMIAH SIMANTEK, 2020)
PDAM Tirtanadi North Sumatra Province is a company that strives to meet the needs of clean water for the community ineach particular area. Along with its development there is a decrease in employee performance which is caused by a lack ofjob satisfaction. This results in employees having less motivation to work as seen from the high level of absenteeism. Inaddition, there is a phenomenon of the lack of activity from the leadership in monitoring the activities of subordinates andthere are employees who feel less empowered in participating in activities. The purpose of this study was to determine andanalyze the influence of leadership and employee empowerment on job satisfaction and its impact on employeeperformance. The population of this study was 250 employees and the sample was drawn using a proportionate stratifiedrandom sampling technique with a total sample of 153 employees. Data analysis using path analysis. The results showedthat leadership and employee empowerment had a positive and significant effect on employee performance and jobsatisfaction was able to mediate the relationship between leadership and employee empowerment on employee performancein PDAM Tirtanadi, North Sumatra Province.